Observation and Simulation of n = 1 Reversed Shear Alfvén Eigenmode on the HL-2A Tokamak. (1st September 2022) - Shi, P. W.; Yang, Y. R.; Chen, W.; Shi, Z. B.; Yang, Z. C.; Yu, L. M.; Wang, T. B.; He, X. X.; Ji, X. Q.; Zhong, W. L.; Xu, M.; Duan, X. R.
Abstract : A branch of high-frequency Alfvénic modes is observed on the HL-2A tokamak. The electromagnetic mode can be driven unstably in the plasma with an off-axis neutral beam heating. Its mode frequency keeps almost unchanged or presents a slow-sweeping behavior, depending on the detail current evolution. The poloidal and toroidal mode numbers are m / n = 1/1. The mode has a quite short duration (≤20 ms) and usually appears 5–10 ms after the neutral beam being injected into the plasma. Hybrid simulations based on M3D-K have also been carried out. The result suggests that co-passing energetic particles are responsible for the mode excitation. The simulated mode structures are localized nearby location of minimum safety factor ( q min ) and agree with the structures obtained through tomography of soft x-ray arrays. Further, the modes are localized in the continuum gap and their frequencies increase with variation of q min in a wide range. Last but not least, the characteristic of unchanged frequency on experiment is also reproduced by the nonlinear simulation with a fixed safety factor. All those evidences indicate that the n = 1 high-frequency mode may belong to a reversed shear Alfvén eigenmode.